A review on thermal fluid management - Arun Prakash J; P. Jayapradha (AG Volumes, 2022)
Thermal fluid management is a critical area in industries that require constant monitoring. If the systems are not managed properly then it will result in catastrophic failures including significant breakdown, replacement, downtime and costs. Though many systems are incorporated to manage the systems ranging from sensors to automatic cut-offs many problems still persist. The non-monetary complications that arise due to the mismanagement of these systems will put lives and livelihoods at risk. The operation of these Thermal fluid heating systems is generally a closed loop but still, the continuous circulation of these thermal fluids/heat transfer fluid operates in a closed loop with the thermal fluid (also referred to as heat transfer fluid) in constant circulation. This constant circulation will also act as heat transfer agents and also their fluid properties tend to change. A special set of control loops are commonly used to monitor these systems. Systems tend to operate mostly in the liquid state and at times there are systems that operate in the vapor state also. Safety, flexibility and efficiency are the key factors when it comes to the management of these systems.